Efeitos do óleo ade neem Azadirachta indica sobre o crescimento in vitro e produção de ocratoxina A por cepas de Aspergillus carbonarius - Mariana Paiva Rodrigues (2019)
Aspergillus carbonarius is a species from the group of black Aspergilli (Aspergillus section Nigri), of world dispersion, regarded as common food spoilage fungi and an important producer of ochratoxin A (OTA). This species is a common contaminant of tropical climate regions. OTA is a toxic secondary metabolite, detected worldwide, mainly biosynthesized by this fungal species, which, when absorbed and metabolized, affects the health of humans and animals through nephrotoxic, hepatotoxic, carcinogenic and immunosuppressive action. Essential oils are volatile complex aromatic substances, constituted by several compounds, which have innumerable distinct positive characteristics like antimicrobial, antioxidant, anti-inflammatory activity; the essential oils and extracts extracted from the Neem tree stand out due to the harmlessness and effectiveness of natural antifungal, antimycotoxin, anti-inflammatory and antioxidant products. This study evaluated the anti-fungal activity of Neem oil, on the growth of six strains of A. carbonarius and the antimycotoxin activity on OTA production. Four concentrations, 0.1%, 0.3%, 0.5% and 1.0% (v/v) of Neem essential oil were added and tested in the culture medium in addition to three different incubation times (2, 7, 10 days). Among the four concentrations of Neem oil evaluated, only 0.3% completely inhibited the growth of A. carbonarius by 98.4% ± 1.0, while the use of the highest tested concentrations of Neem oil, 0.5% and 1.0%, showed lower antifungal activity since these concentrations inhibited only 41.1% ± 5.0 and 64.8% ± 4.5, respectively. The OTA production was completely inhibited with the addition of the lowest concentrations of Neem oil evaluated, 0.1% and 0.3%, for the four strains isolated in the laboratory, from grapes; while the two reference strains tested produced low average levels of OTA in 10 days of incubation. The present study demonstrates that the use of Neem essential oils as an auxiliary method for the reduction of mycelial growth and OTA production is feasible if it is used in adequate concentrations and time.